2018
DOI: 10.33584/jnzg.2018.80.319
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, production and regeneration of subterranean clovers in the Mackenzie Basin, New Zealand

Abstract: The ‘Red Flats’ on Omarama Station in the Mackenzie Basin, has a winter cold, summer dry environment and soils with low plant available water (<60 mm in the top 1 m), and low pH(H2O) (5.2) and high aluminium (8 mg/kg) below 75 mm. The site received 3 t of lime, 300 kg sulphur-super, boron (B), molybdenum (Mo) and herbicides to eliminate hieracium (Hieracium pilosella). Twelve cultivars of subterranean clover (Trifolium subterraneaum), ‘Bolta’ balansa clover (T. michelianum), and perennial ‘Rossi’ red clover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In hill country pastures, soil moisture deficits, i.e., summer drought, negatively impact on the persistence and productivity of white clover (Dodd et al 2001;Knowles et al 2003). Sub clover avoids the summer-dry by remaining as a seed in the soil, but rainfall variability affects persistence (Sheath and Hay 1989) and the length of the growing season (Olykan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In hill country pastures, soil moisture deficits, i.e., summer drought, negatively impact on the persistence and productivity of white clover (Dodd et al 2001;Knowles et al 2003). Sub clover avoids the summer-dry by remaining as a seed in the soil, but rainfall variability affects persistence (Sheath and Hay 1989) and the length of the growing season (Olykan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There was no production from balansa clover as it appeared unable to regenerate after seed set in the first year. Also, the regenerating resident vegetation appeared too competitive in this environment, but annual legumes have been used successfully in a slightly lower rainfall environment at Omarama Station (Olykan et al 2018). The combined mean legume yields of the balansa clover, white clover and lotus plots give an indication of the potential yield from the resident vegetation and the enhancement that has been provided by the introduction of lupins.…”
Section: Discussionmentioning
confidence: 99%
“…Subterranean clover is a highly self-pollinating, diploid (2 n = 16) species ( Ghamkhar et al, 2012 ; Hirakawa et al, 2016 ; Kaur et al, 2017 ). T. subterraneum is a species that is highly utilised in Australia and to a lesser extent in New Zealand ( Nichols et al, 2007 ; Lucas et al, 2015 ; Olykan et al, 2018 ). T. subterraneum is well characterised to perform in dry conditions as it buries its burrs in the soil, allowing seed development to happen underground ( Suckling et al, 1983 ; Widdup and Pennell, 2000 ).…”
Section: Role Of Trifolium Species In New Zealand Pastoral Systemsmentioning
confidence: 99%
“…Trials across New Zealand have been evaluated to select T. subterraneum lines that have improved persistence and dry matter production ( Dodd et al, 1995a , b , c ). Recent studies have identified Australian cultivars that are best adapted to New Zealand dryland pastoral systems ( Lucas et al, 2015 ; Olykan et al, 2018 ). However, more improvement is needed for developing cultivars that fit better to New Zealand environments.…”
Section: History Of Trifolium Breeding In New Zealandmentioning
confidence: 99%